Дневна в.с. стандардна интермитентна хемодијализа - Selim, G; Stojcheva Taneva, O; Grozdanovski, R; Ivanovski, N; Stamatov, L (Македонско лекарско друштво = Macedonian medical association, 2005)
Abstract Hemodialysis is generally performed three times per week, a treatment prescription not based on optimizing the physiology of the normal kidney, thence most hemodialysis patients are, even when treated “adequately” according to current standards, exposed to the so-called unphysiology of dialysis. Standard hemodialysis (HD) is efficient, but intermittent, by contrast, peritonael dialysis generally is continuous, but inefficient. Daily HD is both frequent and efficient and theoretically should be superior to other forms of dialysis for renal replacement therapy. Daily HD has been defined primarily by treatment time and categorized as 1) short daily HD with 6 or more treatments per week and lasts 1.5 – 3.0 h per session and 2) long slow nocturnal daily HD with 6 nights/week and the duration of each session of 6-8 h. Daily HD has been associated with improvements in many outcomes, including blood pressure control, left ventricular hypertrophy and cardiac performance, renal anaemia, hyperphosphatemia control, nutritional state, quality of life and good patient and vascular access survival. The potential problems with daily HD are: logistic (social), economic and medical (deficiency syndromes and blood access). There are no known contra-indications to daily HD. Daily HD represents one of the most revolutionary concepts in the present dialysis treatment, by changing the ratio between duration and frequency of treatment. To assume that 10 – 15 % of standard HD patients could benefit from daily HD. Although experience is still limited, interest is enhanced by positive reports, from all studys.
Daily versus standard intermittent hemodialysis